PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL DALAM LAPORAN TAHUNAN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI PERIODE 2011-2013 - Rani, Resi Prima; Hasan, Amir; Ilham, Elfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the effect of the characteristics of the company to the amount of social responsibility disclosure in the annual report of the company. Disclosure of social responsibility include the environment, energy, safety and health of workers, etc. concerning labor, product, community involvement, and the public. Observation of previous studies showed inconsistencies and generate diversity of results. This study uses four independent variables. These variables are firm size (size), profitability, board size, and the latter is leverage. The sample used in this study was obtained by using purposive sampling method. Its population is 32 Mining Company listed on the Indonesia Stock Exchange (BEI). After deducting the criteria then acquired 29 Company as a sample. Techniques used in the test of the hypothesis of this study is multiple regression analysis with SPSS. Results from this study indicate that company size (size) and the board size is not a significant influence on the disclosure of corporate social responsibility. While profitability and leverage shows significant effects on the disclosure of social responsibility.Keywords: responsibility, company size, profitability, board size, and leverage.